Orígenes y desarrollo de la Facultad de Psicología en UNIFÉ (1963 - 2003) - García García, Victoria (2003)
The article presents a brief revision of the history and development of the Psychology Faculty at Unife; underlining those facts helping to consolidate main advances of the career in our university. The most significant achievements are included and we aware of the importance to continue consolidating our academic commitment.